(untitled) (Jurnal Bahasa, 2007)
Research on meaning from the semantic point of view which describes meaning literally at the sentence structure has caused many problems which have remained unsolved in the Malay language. Describing meaning at the semantic level gives only the literal meaning, which is out qfcontexts and devoid of external inputs of sentences or utterances. Describing meaning at the semantic level becomes more difficult in discussing anomalous phrases which have been used for many years by native speakers. A research, therefore, is carried out exploring a number of V+ 0 phrases in sentences based on an online corpus using the relevance theory as proposed by Sperber and Wilson (1986, 1995). it is thought that by using the relevance theory the problems with regard to the anomalous phrases can be addressed in a critical and practical manner. Pragmatic analysis based on the relevance theomy will also prove that the human cognitive mechanism tends to spontaneously choose the most relevant stimulus. Meanwhile, the receptor mechanism tends to activate the most relevant presumption while the inference mechanism tends to process spontaneously those stimulus in a very productive way only.